Marta Herrera Ángel. El conquistador conquistado. Awás, Cuayquer y Sindaguas en el Pacífico colombiano, siglos XVI-XVIII. (2018)
This deeply researched, intensely thoughtful, and finely illustrated book fills a major void. Whereas the colonial Chocó has received much scholarly attention over the years, little is known of the southwestern corner of Colombia the Spanish called the Province of Las Barbacoas. Even this name is a bit confusing, since for its polyglot indigenous inhabitants, portions of Esmeraldas (Ecuador), some parts of the Patía River drainage, sections of western Pasto, and several major rivers just south of Buenaventura all formed part of a tightly knit but wildly diverse zone of indigenous activity. Home of the famously reclusive Awá-Cuayquer and the ferocious (and presumed extinct) Sindaguas, the colonial Provincia de Las Barbacoas has remained mysterious, both historically and geographically